Strategic Management in Islamic Full Day School ‎Institutional Development in the Era of Artificial ‎Intelligence - M Hadi Prasetyo; Istikomah‎; Eni Fariyatul; Normadiah bin Daud; Engku Ahmad Zaki bin Engku Alwi (State Islamic Institute of Madura, 2023)
Strategic management in the development of Islamic full day school institutions has main components, namely the first organizational environment analysis functions as an early detection and prediction of threats and opportunities, the second analysis of the organizational profile functions as a detection of organizational weaknesses and strengths, the third organizational strategy functions as the achievement of organizational goals.(Nazaruddin 2020). This study uses a qualitative research method with a case study approach. The results of the study show that in strategic management in the development of Islamic full day school institutions in the era of artificial intelligence, there are three things that must be considered, first, strategic management, this process requires a SWOT analysis, carried out thoroughly on the internal and external environment of the school, identifying strengths , weaknesses, opportunities, and threats to future education related to the use of technology. This analysis will facilitate the preparation of the vision and mission as well as targets and programs. Next Second. Institutional Development Strategy, requires a Strategic Plan (RENSTRA), which is a document that contains long-term and short-term goals for future education in the use of Artificial Intelligence (AI) technology. The plan includes specific steps to be taken to integrate future education into the day-to-day activities of the school. And it is necessary to pay attention to the strengthening of fundamentals, strengthening existence and building partnerships and communities. The three Quality Assurance Systems are carried out in a consistent and consistent manner in institutional development, so that the institution is automatically a quality institution. In accordance with the provisions of the ministry of education and culture, the quality assurance system is organized by internal institutions or known as the Internal Quality Assurance System (SPMI) and which is held by the Government as the main person in charge of the education quality system or the External Quality Assurance System (SPME).